Strategy in Increasing Student Learning Interest in History Subjects Senior High School at SMAN 2 Palu - Trisna Ruba; Hasan; Idrus; Wilman D. Lumangino (Journal of Scientific Research, Education, and Technology (JSRET), 2026)
This study aims to analyze the strategies of history teachers in increasing student interest in history at SMA Negeri 2 Palu. The study used a qualitative approach with data collection techniques through observation, interviews, and documentation. The research subjects consisted of history teachers who were directly involved in the learning process. The results showed that teachers implemented various innovative and interactive learning strategies, such as the use of varied learning methods, the use of technology and learning media, group discussions, the provision of rewards, and out-of-class learning activities through visits to historical sites. These strategies were able to increase student enthusiasm, participation, and involvement in history learning. In addition, environmental factors, student character, socioeconomic conditions, and the use of technology also influenced the effectiveness of the learning strategies implemented by teachers. This study concluded that the implementation of creative, flexible, and appropriate learning strategies according to student needs can increase interest in learning history more optimally in the school environment.